National Society of the Colonial Dames of America. Colonial and Pioneer Women Project records - National Society of the Colonial Dames of America
Chiefly essays on the lives of colonial and pioneer women written by members of state organizations and submitted to the society's National Historical Activities Committee. Subjects of the essays are women of local prominence or ancestors of the authors. Sources for the essays include family collections of correspondence, family Bibles, oral histories, local history sources including newspapers and local archives, and published historical works.
A national organization, founded in 1891, composed of women who are descended from an ancestor who came to reside in an American colony before 1750 and whose services were rendered during the Colonial Period.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Indexes available in the Library of Congress Manuscript Reading Room.
Keywords: National Society of the Colonial Dames of America. -- National Historical Activities Committee; Women -- United States -- History; Women colonists -- United States; Women pioneers -- United States; United States -- History, Local